Can high-intensity interval training improve physical and mental health outcomes? A meta-review of 33 systematic reviews across the lifespan - Martland, Rebecca; Mondelli, Valeria; Gaughran, Fiona; Stubbs, Brendon (Journal of sports sciences, 2020)
High-intensity-interval-training (HIIT) has been suggested to have beneficial effects in multiple populations across individual systematic reviews, although there is a lack of clarity in the totality of the evidence whether HIIT is effective and safe across different populations and outcomes. The aim of this meta-review was to establish the benefits, safety and adherence of HIIT interventions across all populations from systematic reviews and meta-analyses. Major databases were searched for systematic reviews (with/without meta-analyses) of randomised & non-randomised trials that compared HIIT to a control. Thirty-three systematic reviews (including 25 meta-analyses) were retrieved encompassing healthy subjects and people with physical health complications. Evidence suggested HIIT improved cardiorespiratory fitness, anthropometric measures, blood glucose and glycaemic control, arterial compliance and vascular function, cardiac function, heart rate, some inflammatory markers, exercise capacity and muscle mass, versus non-active controls. Compared to active controls, HIIT improved cardiorespiratory fitness, some inflammatory markers and muscle structure. Improvements in anxiety and depression were seen compared to pre-training. Additionally, no acute injuries were reported, and mean adherence rates surpassed 80% in most systematic reviews. Thus, HIIT is associated with multiple benefits. Further large-scale high-quality studies are needed to reaffirm and expand these findings. Abbreviations: ACSM: American College of Sports Medicine; BMI: Body Mass Index; BNP: Brain Natriuretic Peptide; BP: Blood Pressure; CAD: Coronary Artery Disease; CHD: Coronary Heart Disease; COPD: Chronic Obstructive Pulmonary Disease; CRP: c- reactive Protein; CVD: Cardiovascular Disease; DBP: Diastolic Blood Pressure; ES: Effect Size; FAS: Reduced Fatty Acid Synthase; FATP-1: Reduced Fatty Acid Transport Protein 1; FMD: Flow Mediated Dilation; Hs-CRP: High-sensitivity c- reactive Protein; HDL: High Density Lipoprotein; HIIT: High-Intensity Interval Training; HOMA: Homoeostatic Model Assessment; HR: Heart Rate; HTx: Heart Transplant Recipients; IL-6: Interleukin-6; LDL: Low Density Lipoprotein; LV: Left Ventricular; LVEF: Left Ventricular Ejection Fraction; MD: Mean Difference; MetS: Metabolic Syndrome; MPO: Myeloperoxidase; MICT: Moderate-Intensity Continuous Training; NO: Nitric Oxide; NRCT: Non-Randomised Controlled Trial; PA: Physical Activity; PAI-1: Plasminogen-activator-inhibitor-1; QoL: Quality of Life; RCT: Randomised Controlled Trial; RoB: Risk of Bias; RPP: Rate Pressure Product; RT: Resistance Training; SBP: Systolic Blood Pressure; SD: Standardised Difference; SMD: Standardised Mean Difference; TAU: Treatment-As-Usual; T2DM: Type 2 Diabetes Mellitus; TC: Total Cholesterol; TG: Triglycerides; TNF-alfa: Tumour Necrosis Factor alpha; UMD: Unstandardised Mean Difference; WC: Waist Circumference; WHR: Waist-to-Hip Ratio; WMD: Weighted Mean Difference Key points: HIIT may improve cardiorespiratory fitness, cardiovascular function, anthropometric variables, exercise capacity, muscular structure and function, and anxiety and depression severity in healthy individuals and those with physical health disorders. Additionally, HIIT appears to be safe and does not seem to be associated with acute injuries or serious cardiovascular events.